The Social Discount Rate : Estimates for Nine Latin American Countries - Lopez, Humberto (World Bank, Washington, DC, 2012)
The social discount rate measures the rate at which a society would be willing to trade present for future consumption. As such it is one of the most critical inputs needed for cost-benefit analysis. This paper presents estimates of the social discount rates for nine Latin American countries. It is argued that if the recent track record in terms of growth in the region is indicative of future performance, estimates of the social discount rate would be in the 3-4 percent range. However, to the extent that the region improves on its past performance, the social discount rate to be used in the evaluation of projects would increase to the 5-7 percent range. The paper also argues that if the social planner gives a similar chance to the low and high growth scenario, the discount rate should be dependent on the horizon of the project, declining from 4.4 percent for a 25-year horizon to less than 4 percent for a 100-year horizon.